Kekuatan Hukum Surat Keterangan Ahli Waris Bagi Anak Luar Kawin dari Pernikahan Tidak Tercatat - Erwinsyahbana, Tengku; Harmita, Harmita (Jurnal Hukum Novelty, 2017)
Based on the Decision of the Constitutional Court Number 46/PUU-VIII/ 2010, a child born from an unregistered marriage may have a civil relationship with his biological father, so as to remain inherited, and to obtain legal certainty as an heir the name of the uregistered marrieage born child should mentioned as the heir. This fact is interesting to be examined and it aims to obtain answers of the legal strength of the heirsâ certificate of unrecorded marriage. This research type is juridical normative with legislation approach through the descriptive-qualitative method. The results of the study indicate that in order to obtain legal certainty, it is supposedly that the certificate of inheritance contains the name of the unrecorded marriage born child. But, this is canât be done, because there is no legislation determines that the childâs name from unregistered marriage could be contained in the letter. So, with no legislation, the certificate of inheritance containing the name of the unregistered marriage child has no legal power, and therefore it is recommended that the government immediately make a regulation concerning the inheritance certificate for the child from unregistered marriage, so it could be clear and fixed.